ANALISIS TINGKAT KELELAHAN TERHADAP SISWA EKSTRAKURIKULER FUTSAL DI SMAN 10 KOTA BEKASI - Akhmad Fikri Azzi Rizqulloh; Febi Kurniawan; Bambang Ismaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the level of fatigue among students futsal extracurricular at SMAN 10 Bekasi City.This research uses a descriptive quantitative approach with a survey research method.The population in this study consists of all the futsal extracurricular participants at SMAN 10 Bekasi City,totaling 40 people.The sampling technique,where the entire population of 40 participants was taken as the sample.This research instrument uses a questionnaire with items that have answers using a Likert Scale, providing four (4) alternative answers: strongly disagree, agree, disagree, Strongly agree. Where in the assessment itself several values are categorized, namely when strongly disagree (1), disagree (2), agree (3), strongly agree (4). The research result show that the level of fatigue among the futsal extracurricular students at SMAN 10 Bekasi City falls into the “very high” category at 5% (2 students), 29 students (73%) in the “high” category, no students in the moderated category, and 2 students (5%) in the “very low” category. It can be cocluded that the level of fatigue among the futsal extracurricular students of SMAN 10 Bekasi City is in the “High” category.